Implementation of a Local Area Network Using a Mikrotik Router on Sheza Computer - Anwar Rifai, Rojani Amsir, Muhammad (JELTec (Journal of Learning Technology), 2024)
As time goes by, the Internet network becomes a staple in implementing networks in educational forums. Internet networks are very important to support the educational process. Having a computer network will facilitate the learning process properly. With a good LAN network, a comfortable lab location will be created, preventing IP conflicts, in the process of analyzing tools when one of the tools is damaged will become easier. LPK Sheza Computer Will Always Improve Quality And Learning Facilities. Local Area Network Is A Computer Network That Connects Two Computers Or More Within The Scope Of One Area, The LAN Network At Sheza Computers Must Be Properly Organized. The data collection process is carried out using the library study method from previous studies, interviews with the leaders of the LPK Sheza Computer, and observations on the LPK sheza computer in order to obtain valid and actual data, the development method uses the NDLC (Network Development Life System) method because by using this method Will Get Effective And Efficient Results. A Good Local Area Network Network Flow Has A Topology That Suits The Needs And The Number Of Devices Owned, With A Good Topology It Will Make It Easy To Manage Devices And Also Detect If There Is Damage To One Of The Tools, The Tools Used Are Routers, Hubs / Switch, UTP Cable, Access Point, And Also Labtop Or Computer.